2011
DOI: 10.1002/chem.201101057
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyaromatic Hydrocarbons from Bis(biaryl)diynes: Large PAHs with Low Clar Sextets

Abstract: A new synthesis of large polyaromatic hydrocarbons (PAHs) with low Clar sextets is reported (see figure). The synthetic protocol involves starting bis(biaryl)diynes, which undergo initial PtCl2‐catalyzed aromatizations, and subsequent 2,3‐dichloro‐5,6‐dicyano benzoquinone (DDQ) oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 29 publications
0
26
1
1
Order By: Relevance
“…104,105 Furthermore, ruthenium-or platinum-catalysed electrophilic cycloaromatization of ortho-alkynylated biaryls is a versatile method to form phenanthrene structures, as represented by the conversion of precursor 24 to [6]phenacene 25, which enabled the synthesis of graphene molecule 26 (C52) through subsequent cyclodehydrogenation (Fig. 56,[106][107][108] Here, ICl-mediated cycloaromatization of ortho-alkynylated biaryls can serve as a metal-free alternative method for obtaining halogenated phenacenes, which can be directly used for further coupling reactions or dehalogenated by simple treatment with n-butyllithium. 56,[106][107][108] Here, ICl-mediated cycloaromatization of ortho-alkynylated biaryls can serve as a metal-free alternative method for obtaining halogenated phenacenes, which can be directly used for further coupling reactions or dehalogenated by simple treatment with n-butyllithium.…”
Section: Synthesis Of Graphene Moleculesmentioning
confidence: 99%
“…104,105 Furthermore, ruthenium-or platinum-catalysed electrophilic cycloaromatization of ortho-alkynylated biaryls is a versatile method to form phenanthrene structures, as represented by the conversion of precursor 24 to [6]phenacene 25, which enabled the synthesis of graphene molecule 26 (C52) through subsequent cyclodehydrogenation (Fig. 56,[106][107][108] Here, ICl-mediated cycloaromatization of ortho-alkynylated biaryls can serve as a metal-free alternative method for obtaining halogenated phenacenes, which can be directly used for further coupling reactions or dehalogenated by simple treatment with n-butyllithium. 56,[106][107][108] Here, ICl-mediated cycloaromatization of ortho-alkynylated biaryls can serve as a metal-free alternative method for obtaining halogenated phenacenes, which can be directly used for further coupling reactions or dehalogenated by simple treatment with n-butyllithium.…”
Section: Synthesis Of Graphene Moleculesmentioning
confidence: 99%
“…This change is energetically unfavorable for [n]acenes with n < 5 or 6, but for larger n values is thermodynamically favorable. Large PAHs with few π-sextets have small HOMO-LUMO energy gaps that facilitate the generation of singlet or triplet open-shell ground states with biradical character (Chen and Liu, 2011). Similar arguments were employed by Einholz and Bettinger to justify the fact that dications of acenes are formed more and more easily with growing size (Einholz and Bettinger, 2013).…”
Section: Biradical Character In Acenesmentioning
confidence: 99%
“…This demonstrates that the higher the number of π-sextets, the larger the HOMO-LUMO gap and the more stable the benzenoid is. In general, fully benzenoids have large HOMO-LUMO gaps (>2.1 eV) and are particularly stable (Chen and Liu, 2011). The 1 H NMR spectrum of kekulene and septulene provided another validation of Clar's aromatic sextets rule (Kumar et al, 2012).…”
mentioning
confidence: 99%
“…3,4 Thus, their ability to transport electrons upon interaction with either an electric field or a photon qualifies them to be potential components in optoelectronic devices. [5][6][7][8] Various PAHs with structures ranging from symmetrical planar 9,10 or contorted [11][12][13][14][15] to less symmetrical 16,17 have been synthesized and studied extensively (see Fig. 1 for representative examples).…”
Section: Introductionmentioning
confidence: 99%
“…21,22 As part of our research on PAH derivatives with tapered symmetry, we reported recently the synthesis and structural characterization of a family of the trapezoidal tribenzo[ fg,ij,rst]pentaphene (TBP) derivatives bearing various aromatic side groups either at their wide or narrow bases. 23,24 Building upon this result, we aimed at synthesizing more laterally extended derivatives than TBP, 25 contorted (c-HBC), 20 less symmetrical (DDHH), 17 (TBTP,2). The higher conjugation of compounds 1 and 2 is expected to lower their respective HOMO-LUMO energy gaps and hence improve their electron/hole charge carrier mobility.…”
Section: Introductionmentioning
confidence: 99%